Demonstrating open superstring amplitude relationship with Yang-mills theory based on dual model limit - Barreiro, Luiz Antonio [UNESP]; de Faria, A. C. Amaro; Canone, A. M. (IOP Publishing, 2019)
This paper demonstrates the relationship between superstrings, Yang-Mills fields, and dual models. We discovered a novel and profound connection between these theories and their respective prescriptions for the calculation of scattering amplitudes, which directly demonstrates the duality between Field Theory and String Theory in a novel manner.
Keywords: Dual limit; Open superstring scattering amplitude; S-Matrix; Yang-Mills theory